2011
DOI: 10.1177/030089161109700106
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy use at the End of Life. A Retrospective Single Centre Experience Analysis

Abstract: Among selected patients who died for advanced cancer in our Operative Unit from 2007 to 2009, 50% received chemotherapy in the last 3 months of life. The availability of palliative care services in the territory of residence of patients can influence the interval between the last chemotherapy administration and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
16
1
Order By: Relevance
“…However, the proportion of terminal cancer patients receiving palliative chemotherapy in the last six months of life is much higher than in the United States where Emanuel et al [10] reported a rate of 26-33% in 2003. The proportion of the use of palliative chemotherapy in metastatic or advanced solid cancer patients in the last two weeks of life has been decreasing (18.5% in North America in 2004, 8% in Australia in 2009, and 6% in Italy in 2011) [11-13]. However, in our study, the use of palliative chemotherapy in the last two weeks of life was 9.5%, still higher than in other countries.…”
Section: Discussioncontrasting
confidence: 50%
“…However, the proportion of terminal cancer patients receiving palliative chemotherapy in the last six months of life is much higher than in the United States where Emanuel et al [10] reported a rate of 26-33% in 2003. The proportion of the use of palliative chemotherapy in metastatic or advanced solid cancer patients in the last two weeks of life has been decreasing (18.5% in North America in 2004, 8% in Australia in 2009, and 6% in Italy in 2011) [11-13]. However, in our study, the use of palliative chemotherapy in the last two weeks of life was 9.5%, still higher than in other countries.…”
Section: Discussioncontrasting
confidence: 50%
“…Other parameters were described less frequently as being associated with near-death chemotherapy: symptomatic disease, poor ECOG PS, dying in a small hospital (<1000 beds) 66 70. On the other hand, to be included in a therapeutic trial did not seem to influence the interval between chemotherapy and death 59. Less invasive oral treatments (targeted therapies, chemotherapies), often better tolerated, can easily be maintained at the EOL 74.…”
Section: Resultsmentioning
confidence: 99%
“…That step identified 150 references. The second step was restricted to articles analysing—at least in part—lung cancers, excluding case reports and general reviews; it found 42 publications examining one or several indicators of EOL-care aggressivity of patients with lung cancer that were read in their entirety 11 14 16 23–65…”
Section: Methodsmentioning
confidence: 99%
“…(a) Disease and clinical factors: Key factors in decisions to stop treatment included worsening patient condition or functional status [ 10 , 38 , 43 , 44 , 49 , 52 , 55 , 57 60 ] disease progression or advanced stage disease [ 9 , 38 , 40 , 43 , 44 , 47 , 49 , 52 , 57 , 60 ] and treatment side effects [ 7 , 38 , 49 , 52 , 55 , 59 61 ]. Patients who received their diagnosis when only in advanced disease, and patients who had not received treatment earlier in the course of illness for other reasons, often had their therapy extended much longer than patients who had received earlier treatments [ 5 , 38 , 62 65 ].…”
Section: Resultsmentioning
confidence: 99%